Systematic Review of Data Governance Practices in Multi-Cloud Product Delivery and Public Service Transformation - Bolanle A. Adewusi; Bolaji Iyanu Adekunle; Sikirat Damilola Mustapha; Abel Chukwuemeke Uzoka (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
As digital transformation accelerates across industries and government sectors, multi-cloud environments have become essential for flexible, scalable, and resilient IT operations. However, this paradigm shift presents complex challenges related to data governance, especially in contexts where product delivery and public service transformation depend on the seamless, secure, and compliant management of distributed data. This systematic review investigates emerging data governance practices tailored for multi-cloud architectures and evaluates their effectiveness in supporting innovation, operational continuity, and public trust in both private and public sector domains. Drawing from peer-reviewed literature, industry frameworks, and real-world case studies, the review explores key governance dimensions including data ownership, lineage, interoperability, security, privacy, and regulatory compliance. Special emphasis is placed on how organizations adapt their data governance models to accommodate multi-cloud complexities, such as cross-platform data movement, vendor-specific policy conflicts, and decentralized access control mechanisms. The study also examines enabling technologies like data fabric, policy automation, metadata management, and AI-driven governance tools that support real-time visibility and control in hybrid cloud environments. Findings reveal that successful data governance in multi-cloud contexts depends not only on robust technological infrastructure but also on clear organizational policies, stakeholder collaboration, and adaptive governance frameworks. Public sector initiatives leveraging multi-cloud solutions for digital service delivery demonstrate that agile governance models, citizen-centric data policies, and strong ethical oversight are pivotal to achieving transparency, accountability, and responsiveness. This review concludes that while multi-cloud environments pose inherent governance risks, they also offer unprecedented opportunities to reimagine data stewardship and service innovation. The paper recommends a comprehensive governance strategy integrating policy harmonization, cross-cloud observability, continuous compliance monitoring, and inclusive stakeholder engagement. By advancing data governance maturity in multi-cloud setups, organizations can unlock greater value from their digital assets and ensure secure, equitable, and innovative service outcomes.